Cooperative Innovation, Coworking, and the Fluminense Craftbeer Market Beer (Gestão & Regionalidade, 2021)
Coworking systems are spaces that offer flexibility to their users concerning costs, and, therefore, their main actors are freelancers or/and startups. Gypsy breweries are breweries without factories that produce in the space of the other brewery, and it can be considered a coworking model. Coworking Fluminense brewers create partnership relationships to make their craft beer. This work sought to identify the contribution of craft breweries to the theory of collaborative innovation and the beer market, for this used bibliographic, documentary research and in-depth interviews, and a survey. We analyzed the results qualitatively and through descriptive statistics. 154 Fluminense microbreweries were researched, with 15 interviews and 37 questionnaires collected. It observed collaborative innovation in beer coworking allows small companies to develop their product and enter the market. As well as the introduction of new partnerships promotes the strengthening of the dissemination of craft beers among consumers in the state of Rio de Janeiro, at the same time, which expands this market to investors, distributors, commercial promoters, and other beer producers
Keywords: cooperative innovation; coworking; gypsy craft beer